HGF/c-Met Axis: The Advanced Development in Digestive System Cancer - Shao, Zhiwei; Pan, Haoqi; Tu, Sheng; Zhang, Jingying; Yan, Sheng; Shao, Anwen (Frontiers in Cell and Developmental Biology, 2020)
Numerous studies have indicated that abnormal activation of the HGF/c-Met signaling pathway can lead to cell proliferation, invasiveness, and metastasis of cancers of the digestive system. Moreover, overexpression of c-Met has been implicated in poor prognosis of patients with these forms of cancer, suggesting the possibility for HGF/c-Met axis as a potential therapeutic target. Despite the large number of clinical and preclinical trials worldwide, no significant positive success in the use of anti-HGF/c-Met treatments on cancers of the digestive system has been achieved. In this review, we summarize advanced development of clinical research on HGF/c-Met antibody and small-molecule c-Met inhibitors of cancers of the digestive system and provide a possible direction for future research.